The effects of paternalistic leadership on new generation employees' job satisfactions and turnover intention - Shu Guohua (2023)
Based on the social exchange theory, this study explores the influence mechanism and boundary conditions of paternalistic leadership (authoritarian leadership / benevolent leadership / moral leadership) on the relationship between employee job satisfaction and turnover intention. Through a three-wave time-lagged questionnaire data of 345 new-generation employees in eight companies, the results of this study show that: participative safety and communication quality play a mediating role in the relationship between paternalistic leadership and employee job satisfaction, and between paternalistic leadership and employee turnover intention. Perceived organizational support moderates the impacts of benevolent leadership on participative safety and communication quality, and the impact of moral leadership on communication quality. This study enriches the research on paternalistic leadership, and increases our understanding of social exchange theory. The conclusions have important practical implications for organizations to effectively manage the new generation of employees.